THE PORTRAYAL OF WOMEN EMPOWERMENT THROUGH THE MAIN CHARACTER IN NORTH COUNTRY MOVIE - Wulandari, Tri Oetari; Surya, Satyawati; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The purpose of the study is to identify the kinds of women empowerment dimension portrayed in the movie through Josey as the main female character. Women empowerment has been an issue of immense discussion and contemplation over the last few decades worldwide. This research discusses about women’s empowerment in North Country movies, and investigates further about Josey Aiems as the main character that showed women power in this movie. In addition, Jo Rowland’s theory is employed as the main theoretical basis to answer the research question. The main data of this research were the dialogues, characters’ characters’ attitudes and beliefs that were related to the research questions in this research. The results of the study are based on the analysis of the research questions about dimension empowerment which is personal, relational and collective to support the empowerment of others in community the dimension makes the power getting stronger than before, and women become able to organize themselves to increase their independent right to make choices.